Factors and mechanisms that influence the reactivity of trivalent copper: A novel oxidant for selective degradation of antibiotics. (1st February 2019) - Feng, Yong; Qing, Weihua; Kong, Lingjun; Li, Hailong; Wu, Deli; Fan, Yiang; Lee, Po-Heng; Shih, Kaimin
Abstract: Trivalent copper complexes are active intermediates in aquatic redox reactions that involve copper ions or structural copper, but their reactivity and selectivity toward pollutants remain unknown. We characterized copper(III) periodate, a representative trivalent copper compound, with phenol and several antibiotics as model contaminants. The results show that Cu(III) is highly reactive to phenol degradation; near-complete degradation was achieved after 10 min at a molar ratio of 3:1 (Cu[III]: phenol). Common alcohols, including methanol and 2-propanol, showed pH-dependent reactivity for Cu(III). In contrast to aquo trivalent copper ions that react rapidly with tert-butanol, Cu(III) showed limited reactivity toward tert-butanol. A mechanistic investigation showed that the degradation was caused by direct oxidation by Cu(III) and that no hydroxyl radicals were involved. Common water components such as chloride ions did not influence the reaction, which suggests that the use of Cu(III) may help mitigate the generation of chlorinated products. As a one-electron oxidant, Cu(III) showed high reactivity to degrade electron-rich compounds; the concentrations of sulfamethazine, sulfamethoxazole, and sulfadiazine (100 μg/L) were reduced to 1.8, 7.5, and 42.5 ng/L, respectively, after 2 min of reaction with 10 μM Cu(III). These results demonstrate a novel and highly efficient oxidant for selective removal of ubiquitous micropollutants from water bodies. Graphical abstract: Image 1 Highlights: Cu(III) was used to degrade a variety of contaminants. The reactivity and selectivity of Cu(III) were investigated. No hydroxyl radicals were involved in the degradation by Cu(III). Cu(III) showed high reactivity to degrade electron-rich compounds. Common water components such as chloride ions did not influence the degradation.